Conversion from Laparoscopic to Open Cholecystectomy - Shrestha, Samir; Shah, Surendra S; Poudyal, Sanjay; Shah, Jay N; Jaiswal, Vijay Kumar (Journal of Patan Academy of Health Sciences, 2015)
Introductions: With the advent of newer technology, the era of open surgery for gall bladder diseases has been preferably taken over by laparoscopic cholecystectomy. However, certain cases still require conversion to open surgery. In this review we aim to analyze the reason for conversion. Methods: This retrospective study was conducted at Patan Hospital, Patan Acdemy of Health Sciences, Nepal. All patients who underwent laparoscopic cholecystectomy from February 2009 to July 2012 were included in the study. File numbers of all the patients were obtained from operation room register. The patient files were analyzed for age, sex, duration of symptoms, liver function tests, ultrasound findings and the description in operation note for reason for conversion. Results: The age ranged from 12 to 81 years with mean age of patients 32.76 years and male to female ratio 1:2.9. The mean operating time was 65 minutes and average post operative hospital stay was 1.61 days. Out of 305 patients, 34 (11.14%) required open conversion. Factors responsible for open conversion were dense fibrosis at Calots in 11 (3.6%), adhesions due to previous abdominal surgery in 6 (1.9%), uncontrollable bleeding in 5 (1.6%), bile duct injury in 4 (1.3%) cholecystoenteric fistula in 3 (0.9%), Mirizzi’s syndrome 2(0.6%). Conclusions: Adhesions at the calot’s triangle was the common reason for conversion from laparoscopic to open cholecystectomy. Plain Language Summary: This study was conducted to determine the predictive factors for conversion of laparoscopic cholecystectomy. The study found that dense adhesion around calot’s triangle and adhesions pertaining to previous abdominal surgery were the main reasons for conversion to open surgery. So, before embarking on laparoscopic cholecystectomy, it is essential to take detail history and examination, to rule out the probable cause of conversion beforehand and minimize; morbidity, duration of surgery and cost. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13013 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):30-32